Ellipsis in the Light of Text Linguistics - Mesdaq, Mohamed Al-Amin (El Omda in Linguistics and Discourse Analysis, 2019)
In the Seventies of the last century a new knowledge branch was established in the Department of Linguistics, it made the text the field of the study and the subject of research. It focused its attention on the tools and mechanisms that achieve its cohesion. In this article we try to identify the Ellipsis, which is one of the grammatical tools that contribute to the consistency of texts, by standing on its concept, its sections, its role in achieving the cohesion of the text, and the role of the recipient in extracting the deleted items and link the text's network to each other.